LEGAL CERTAINTY OF THE MEANING OF STRATEGIC DECISIONS IN LIMITING THE AUTHORITY OF THE REGENT'S EXECUTING DUTIES IN THE FIELD OF PERSONNEL AFFAIRS - Ni Nyoman Inda Yunita Nadia In Putri; Siti Kotijah; Ine Ventyrina; Warkhatun Najidah (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
This study analyzes the legal certainty of the meaning of strategic decisions in limiting the authority of the acting regent in the field of personnel. The research method used is doctrinal research with a statutory approach and a case approach. The results of the study indicate that legal certainty regarding the meaning of